Preparation, Characterization, and Biological Evaluation of New Schiff Base Ligand and their Complexes with iron(II), cobalt(II), nickel(II) and Copper(II) Ions - Mohammed Hamid Said (Journal of Global Pharma Technology, 2016)
In the present work a new schiff base ligand was prepared by reaction of 6-amino penicillinic acid with 5-chlorosalicyldehde. The new ligand was characterized by using various techniques UV/ Visible, FT IR , Mass spectral ,1H NMR, and 13C NMR , It was also preparing four new complexes by interaction of ligand with transition metals ions ( Fe2+, Co2+, Ni2+, Cu2+ ) and characterized by UV/ Visible, FT IR, Magnetic moment and molar conductance. Ligand shows tridentate behavior demonstrated by the presence of three effective groups and complexes have taken octahedral form. The biological effectiveness was measured for ligand and coordination complexes against two types of bacteria ( Staphyllococcus aureus and Pseudomonas aeruginosa ) showed good effectiveness.Keyword: β-Lactam, Schiff base, 6.Amino Penicillinic, and tridentate ligand.